Microstructural Changes Of Aluminium Alloy A319 On Cooling Slope Plate - Ahmad Muhammad, Aziz; Mohd Zaidi, Omar; Zainuddin, Sajuri; Mohd Shukor, Salleh (Penerbit UTM Press, 2016)
The cooling slope (CS) casting process is one of the simplest methods for producing a non-dendritic microstructure. To more clearly determine how this microstructure is formed, specifically in A319, requires an examination of how the dendritic microstructure evolves along the entirety of the CS plate. Yet until now, there are still unclear on the verification of microstructures changes on the CS plate. Based on experimental results, this paper offers an explanation for the mechanism involved in producing a nearly globular microstructure in A319. In addition, the mechanism is verified by using the planimetry method. Moreover a quantitative method is used to determine the grain size and shape factor to provide further support for the proposed mechanism. The solid fraction of α-Al at the impact zone is 70 % which is the highest compared to other zones. Grain size and shape factor shown a decreasing and increasing value respectively from the impact zone until the bottom zone.